2021
DOI: 10.1093/jae/ejab006
|View full text |Cite
|
Sign up to set email alerts
|

Are We Really Painting the Devil on the Walls? Polarization and Its Drivers in Sub-Saharan Africa in the Past Two Decades

Abstract: The development path of Sub-Saharan Africa (SSA) over the past two decades has been characterized by sluggish poverty reduction occurring alongside robust economic growth. Applying polarization measures to comparable survey data from 24 SSA countries, we find that there has been a generalizable increase in polarization over the past two decades—and in particular, an increased concentration of households in the lower tail of the welfare distribution of SSA countries. The polarization process is further analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Starting precisely with the distinction between the analysis of income inequality and polarization, the paper adds to the scant literature present for the latter issue (D'Ambrosio 2001;Gradín 2000;Hussain 2009;Brzezi ński 2011;Poggi and Silber 2010). Further, it observes polarization using a method (i.e., relative distribution) hitherto sparsely employed for European countries, with few exceptions (Petrarca and Ricciuti 2016;Nissanov and Pittau 2016), which allows us to observe how incomes are distanced from each other from an absolute rather than relative point of view (Clementi et al 2022b), as shown by other indexes proposed in previous research.…”
Section: Discussionmentioning
confidence: 92%
“…Starting precisely with the distinction between the analysis of income inequality and polarization, the paper adds to the scant literature present for the latter issue (D'Ambrosio 2001;Gradín 2000;Hussain 2009;Brzezi ński 2011;Poggi and Silber 2010). Further, it observes polarization using a method (i.e., relative distribution) hitherto sparsely employed for European countries, with few exceptions (Petrarca and Ricciuti 2016;Nissanov and Pittau 2016), which allows us to observe how incomes are distanced from each other from an absolute rather than relative point of view (Clementi et al 2022b), as shown by other indexes proposed in previous research.…”
Section: Discussionmentioning
confidence: 92%
“…The subject matter and methodology inClementi et al (2021) are the same as those presented inClementi et al (2022a).…”
mentioning
confidence: 99%